SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI TERBAIK PADA KANTOR BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA METRO DENGAN METODE TOPSIS DAN FUZZY - Septiani, Debi Dwi; Apsiswanto, Untoro; Yusuf, Ridwan (UNIVERSITAS DHARMA WACANA, 2024)
In the decision-making process it will affect the Performance Allowance, the criteria set by the agency, starting from discipline, loyalty, attendance, and performance. To be able to process more objective assessment data using the Topsis and Fuzzy Methods which have a simple and easy-to-understand concept, this simplicity is seen from the process flow of the TOPSIS method which is not so complicated. Because it uses criteria indicators and alternative variables as helpers to determine decisions while the Fuzzy Method is capable of linguistic reasoning processes, so that in its design there is no need for mathematical equations of controlled objects and applying the results of the design into a web-based system. The software design technique method used in designing this system uses the SDLC Model Developer method used is the Waterfall Model for the Communication, Planning, Modeling, Construction and Deployment stages. This application is made using the programming language PHP, HTML and MySQL database. This application is able to produce the best employee data every month.Keywords: SPK, best employee, TOPSIS, Fuzzy, SDLC, Waterfall.